The urban poor: profile and constraints affecting their participation in allotment gardens. Issue 3 (3rd April 2023) - Houessou, Mawuna D.; Sonneveld, Ben G. J. S.; Aoudji, Augustin K. N.; Thoto, Fréjus S.; Snelder, Denyse J. R. M.; Adegbidi, Anselme A.; De Cock Buning, Tjard
ABSTRACT: Rapid global urbanisation has seen a growing number of urban poor who lack natural endowments to cope with food shortages. Broadening their safety nets merits urgent political attention but requires understanding their profiles. A survey among 88 urban poor in Benin found that they had low educational and income levels, overcrowded and unsanitary housing conditions, and limited access to social services and health facilities; 76 per cent of them were food insecure, influenced by city, gender, ownership of a motorbike, and access to health facilities. Engaging them in allotment gardens requires farming skills, financial capital, and safety issues.